Penggunaan Gambar untuk Mengarang Teks Deskriptif secara Koheren dan Kesatuan - Muchamad Arif (Universitas Narotama, 2018)
Pictures are language teaching aids that can make students love to write. They have an idea to write. They can describe what they see. This study focuses on the coherence and unity of student descriptive essay written based on the picture. There are several ways to know how coherence and how the unity of a paragraph. For coherence, there are noun repeats, use of pronouns, use of transitions, and setting sentences in a logical order. On the other hand, for unity, the author only discusses one main idea. The research design used is descriptive qualitative. This study was conducted in three meetings. Each meeting, the students get a different picture. Next, they should write and collect at the end of the meeting. Then, the words, phrases, and sentences written by students are analyzed. Furthermore, it was analyzed descriptively. From the results of student essay, it can be seen that there is a significant improvement on the ability of students in writing descriptive text. It seems that the use of images can help students to write descriptive text. The picture can give them an illustration of what they will write. Keywords: Picture, descriptive text, coherence, unity